Deteksi Cemaran Total Bakteri, Coliform, Escherichia coli, dan Salmonella sp. pada Daging Ayam Broiler (Gallus domesticus) yang Dijual di Beberapa Pasar Daerah Kabupaten Badung, Bali - Kadek Aryndha Sukma Prabaswari; Retno Kawuri; Dwi Ariani Yulihastuti (Metamorfosa: Journal of Biological Sciences, 2024)
Chicken meat is a source of animal protein which is easily damaged due to its high water content. Chicken meat that is bought and sold could potentially become a place for the growth of bacteria that cause foodborne diseases.This study aims to determine total bacterial contamination, Coliform, Escherichia coli, and Salmonella sp. on broiler chicken meat in Badung Regency and determine the suitability of broiler chicken meat samples following food safety standards. Samples were taken using a purposive sampling method in six sub-districts in Badung Regency, namely Petang, Abiansemal, Mengwi, North Kuta, Kuta and South Kuta sub-districts at traditional markets that sell broiler chicken meat. The samples were tested using the pour plate and streak platting method. Parameters tested include Total Plate Number (ALT), Coliform, Escherichia coli, and Salmonella sp. on broiler chicken meat samples. Coliform and Escherichia coli bacteria were detected using Petrifilm ready-to-use media, while Salmonella sp. tested on selective Salmonella-Shigella Agar (SSA) media and catalase test and Gram staining. The research result showed that the contamination rates in broiler chicken breast meat were: Total Plate Number (ALT) 105 CFU/g to 107 CFU/g; Coliform and Escherichia coli 101 CFU/g to 104 CFU/g; Salmonella sp. positive in all samples, so that the samples tested did not meet the safety quality requirements for chicken meat according to SNI 3924: 2009.